DEVELOPING INTERCULTURAL COMPETENCE THROUGH EDUCATION (Proceedings of International Educators Conference, 2023)
Language is a means of forming and storing ideas as reflections of reality and exchanging them in the process of human intercourse. Language is social by nature; it is inseparably connected with the people who are its creators and users; it grows and develops together with the development of society.